Programmable manipulation of oligonucleotide–albumin interaction for elongated circulation time. Issue 6 (16th March 2022) - Yang, Cai; Zhao, Haitao; Sun, Yang; Wang, Cheng; Geng, Xinyao; Wang, Ruowen; Tang, Lumin; Han, Da; Liu, Jianjun; Tan, Weihong
Abstract: Oligonucleotide (ON) therapeutics are emerging as a new generation of medicine with tremendous potential, but their clinical translation is hampered by inferior stability and short circulation time in the human body. Here, we report a general approach to manipulating the interaction between ONs and albumin by modulating hydrophobicity. A series of DNA aptamer derivatives were designed and prepared by programmable synthesis as an ON library with a gradient of hydrophobic base 'F'. In vitro experiments revealed that the introduction of two F bases at both ends of ONs enhanced the biostability without sacrificing biological activities, while the binding affinity toward albumin was dramatically increased with K d in the range of 100 nM to 1 μM. In vivo imaging confirmed the immediate formation of the aptamer–albumin complex after the injection, and the circulation time of the aptamer was dramatically elongated owing to the enhanced biostability and retarded renal excretion. The programmable incorporation of the F base provides a general approach to regulating albumin-binding affinity and enhancing the stability of aptamers in vivo, conferring aptamer therapeutics prolonged circulation time to meet clinical requirements.